Insulin receptor substrate 1 may play divergent roles in human colorectal cancer development and progression - Lomperta, Karolina (World J Gastroenterol, 2020)
BACKGROUND: Despite effective prevention and screening methods, the incidence and mortality rates associated with colorectal cancer (CRC) are still high. Insulin receptor substrate 1 (IRS-1), a signaling molecule involved in cell proliferation, survival and metabolic responses has been implicated in carcinogenic processes in various cellular and animal models. However, the role of IRS-1 in CRC biology and its value as a clinical CRC biomarker has not been well defined. AIM: To evaluate if and how IRS-1 expression and its associations with the apoptotic and proliferation tumor markers, Bax, Bcl-xL and Ki-67 are related to clinicopathological features in human CRC. METHODS: The expression of IRS-1, Bax, Bcl-xL and Ki-67 proteins was assessed in tissue samples obtained from 127 patients with primary CRC using immunohistochemical methods. The assays were performed using specific antibodies against IRS-1, Bax, Bcl-xL, Ki-67. The associations between the expression of IRS-1, Bax, Bcl-xL, Ki-67 were analyzed in relation to clinicopathological parameters, i.e., patient age, sex, primary localization of tumor, histopathological type, grading, staging and lymph node spread. Correlations between variables were examined by Spearman rank correlation test and Fisher exact test with a level of significance at P < 0.05. RESULTS: Immunohistochemical analysis of 127 CRC tissue samples revealed weak cytoplasmatic staining for IRS-1 in 66 CRC sections and strong cytoplasmatic staining in 61 cases. IRS-1 expression at any level in primary CRC was associated with tumor grade (69% in moderately differentiated tumors, G2 vs 31% in poorly differentiated tumors, G3) and with histological type (81.9% in adenocarcinoma vs 18.1% in adenocarcinoma with mucosal component cases). Strong IRS-1 positivity was observed more frequently in adenocarcinoma cases (95.1%) and in moderately differentiated tumors (85.2%). We also found statistically significant correlations between expression of IRS-1 and both Bax and Bcl-xL in all CRC cases examined. The relationships between studied proteins were related to clinicopathological parameters of CRC. No significant correlation between the expression of IRS-1 and proliferation marker Ki-67, excluding early stage tumors, where the correlation was positive and on a high level (P = 0.043, r = 0.723). CONCLUSION: This study suggests that IRS-1 is co-expressed with both pro- and antiapoptotic markers and all these proteins are more prevalent in more differentiated CRC than in poorly differentiated CRC.